Authigenic carbonate mineral formation in the Pagassitikos palaeolake during the latest Pleistocene, central Greece - Karageorgis, Aristomenis P (2012)
The Pagassitikos Gulf in Greece is a semi-enclosed bay with a maximum depth of 102 m. According to the present-day bathymetric configuration and the sea level during the latest Pleistocene, the gulf would have been isolated from the open sea, forming a palaeolake since ~32 cal. ka b. p. Sediment core B-4 was recovered from the deepest sector of the gulf and revealed evidence of a totally different depositional environment in the lowest part of the core: this contained light grey-coloured sediments, contrasting strongly with overlying olive grey muds. Multi-proxy analyses showed the predominance of carbonate minerals (aragonite, dolomite and calcite) and gypsum in the lowest part of the core. Carbonate mineral deposition can be attributed to autochthonous precipitation that took place in a saline palaeolake with high evaporation rates during the last glacial-early deglacial period; the lowest core sample to be AMS 14C dated provided an age of 19.53 cal. ka b. p. The palaeolake was presumably reconnected to the open sea at ~13.2 cal. ka b. p. during the last sea-level rise, marking the commencement of marine sedimentation characterised by the predominance of terrigenous aluminosilicates and fairly constant depositional conditions lasting up to the present day.